Comparative Analysis of Host Cell Entry Efficiency and Neutralization Sensitivity of Emerging SARS-CoV-2 Lineages KP.2, KP.2.3, KP.3, and LB.1 - Nianzhen Chen; Katharina Emma Decker; Sebastian R. Schulz; Amy Kempf; Inga Nehlmeier; Anna-Sophie Moldenhauer; Alexandra Dopfer-Jablonka; Georg M. N. Behrens; Metodi V. Stankov; Luis Manthey; Hans-Martin Jäck; Markus Hoffmann; et al. (Vaccines)
New SARS-CoV-2 lineages continue to evolve and may exhibit new characteristics regarding host cell entry efficiency and potential for antibody evasion. Here, employing pseudotyped particles, we compared the host cell entry efficiency, ACE2 receptor usage, and sensitivity to antibody-mediated neutralization of four emerging SARS-CoV-2 lineages, KP.2, KP.2.3, KP.3, and LB.1. The XBB.1.5 and JN.1 lineages served as controls. Our findings reveal that KP.2, KP.2.3, KP.3, and LB.1 lineages enter host cells efficiently and in an ACE2-dependent manner, and that KP.3 is more adept at entering Calu-3 lung cells than JN.1. However, the variants differed in their capacity to employ ACE2 orthologues from animal species for entry, suggesting differences in ACE2 interactions. Moreover, we demonstrate that only two out of seven therapeutic monoclonal antibody (mAbs) in preclinical development retain robust neutralizing activity against the emerging JN.1 sublineages tested, while three mAbs displayed strongly reduced neutralizing activity and two mAbs lacked neutralizing activity against any of the lineages tested. Furthermore, our results show that KP.2, KP.2.3, KP.3, and LB.1 lineages evade neutralization by antibodies induced by infection or vaccination with greater efficiency than JN.1, particularly in individuals without hybrid immunity. This study indicates that KP.2, KP.2.3, KP.3, and LB.1 differ in ACE2 interactions and the efficiency of lung cell entry and suggest that evasion of neutralizing antibodies drove the emergence of these variants.